Corporate environmental disclosure and market value. Do board independence matter? - Shawai, Aliyu Sani; Lok, Char Lee; Jalaludin, Dayana (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: This paper aims to examine the relationship between three measures of corporate environmental disclosure and market value using Nigerian non-financial listed companies. The paper also explores the effect of the moderating role of board independence.Methodology: We use DICTION software to obtain the measurements of environmental disclosure volume, general disclosure tone, and specific disclosure tone, as well as regression analysis using the GMM model to take care of endogeneity issues.Results and conclusion: The empirical studies revealed that general environmental disclosure and specific environmental disclosure have a positive and statistically significant impact on the Tobin’s Q. We document that board independence positively moderates the relationship between general and specific environmental disclosure on Tobin’s Q. We recommend that firms should focus on environmental responsibility reporting as a driver for better performance and value enhancement and that it will help to achieve SDG 12 as enshrined in the United Nations SDGs 2030 agenda. The paper considers only the environmental dimension of sustainability with the use of only non-financial listed Nigerian companies for twelve (12) years (2011-2022).Implication of findings: Management, investors, professionals, policymakers and authorities should consider the environmental disclosure requirements for proper informed decisions. The study tests the progress in achieving the sustainable development goals (SDG 12) as well as the role of the moderating variable of board independence in Nigerian listed non-financial firms.
Keywords: Environmental Disclosure; Board independence; Tobin's Q; Stakeholder theory; Diction Software